Making work more equal: A new labour market segmentation approach - Damian Grimshaw; Colette Fagan; Gail Hebson; Isabel Tavora (Manchester University Press, 2017)
This book is inspired by, and dedicated to, Jill Rubery. Jill is a major figure in international debates on inequalities in work and employment. Her intellectual contributions are renowned for both their critical questioning of mainstream theoretical approaches, whether in economics, management, industrial relations or comparative systems, and their attention to real-world empirical detail. Jill's intellectual roots are with the influential Cambridge economics group researching labour market segmentation in the late 1970s and 1980s during a period when Keynesian economic thought was being eclipsed by neoclassical economics modelling. The research was inter-disciplinary, grounded in data (mostly involving case studies of firms) and driven by an ambitious intellectual agenda that developed theory while also illuminating practical matters of relevance to policy-makers and practitioners.
Keywords: 330; Inequalities; Work; Employment; Economics; New approach; New Labour